PsycEXTRA Dataset 2007
DOI: 10.1037/e529832013-001
|View full text |Cite
|
Sign up to set email alerts
|

On perceived exertion and its measurement

Abstract: The general aim of the thesis is to answer questions on general and differential aspects of perceived exertion and on the measurement of its intensity variation. Overall perceived exertion is commonly treated as a unidemensional construct. This thesis also explores its multidimensional character. Four empirical studies are summarized (Study I-IV). Psychophysical power functions of perceived exertion obtained with the new improved Borg CR100 (centiMax) scale were found to be consistent with results obtained wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 88 publications
(126 reference statements)
0
49
1
4
Order By: Relevance
“…However, Saris et al (2003) showed that men engaged in more vigorous activities than females. In contrast, Borg (2007) found that females reported higher perceived exertion than males under the same workload.…”
Section: Discussioncontrasting
confidence: 47%
See 2 more Smart Citations
“…However, Saris et al (2003) showed that men engaged in more vigorous activities than females. In contrast, Borg (2007) found that females reported higher perceived exertion than males under the same workload.…”
Section: Discussioncontrasting
confidence: 47%
“…The range of the scale is structured such that a rating of 6 corresponded to 60 beats per minute and 20, being the highest score, corresponded to 200 beats per minute (Atchley, 2011). Borg (2007) confirmed the validity of the RPE in measuring perceived intensity using physiological and self-report measures. Strong correlations were found between heart rate and RPE (r =.80 to .90; Atchley, 2011).…”
Section: Rate Of Perceived Exertion (Rpe)mentioning
confidence: 65%
See 1 more Smart Citation
“…Borg's CR-10 scale was developed for rating subjective symptoms from 0 to 10 with the numbers anchored by verbal expressions; i.e., 0 is nothing at all, 5 is strong, and 10 is extremely strong -maximal [15]. This scale was used as a subjective assessment of fatigue in other fatiguerelated studies [14,[18][19][20].…”
Section: Subjective Rating Scalementioning
confidence: 99%
“…Subjective data were collected using Borg's CR-10 scale at the second hour and at the end of work. Borg's CR-10 scale has been suggested to determine perceived exertion such as fatigue, especially in work tests [15].…”
Section: Introductionmentioning
confidence: 99%